2002
DOI: 10.1177/011542650201700138
|View full text |Cite
|
Sign up to set email alerts
|

Energy Requirements in Critically Ill Patients: How Close Are Our Estimates?

Abstract: A retrospective analysis of 55 mechanically ventilated critically ill patients was conducted to determine adequacy of nutritional support (total parenteral nutrition or enteral nutrition) according to requirements established by indirect calorimetry. Patients who received 90% to 110% of the established energy requirements as measured by indirect calorimetry were defined as adequately fed. At the time of the indirect calorimetry measurements, all patients were receiving their targeted nutritional support, as as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…For example, McClave et al (1998) and Alberda et al (2002) have estimated requirements by adding 10 % to REE measured by metabolic cart, whereas Kan et al (2003) have estimated the requirements by adding 20 % to REE. As a result of the differences in how the energy requirements have been estimated, there are considerable differences in the reported rates of 'overfeeding'.…”
Section: Discussionmentioning
confidence: 99%
“…For example, McClave et al (1998) and Alberda et al (2002) have estimated requirements by adding 10 % to REE measured by metabolic cart, whereas Kan et al (2003) have estimated the requirements by adding 20 % to REE. As a result of the differences in how the energy requirements have been estimated, there are considerable differences in the reported rates of 'overfeeding'.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of nutrition support in the ICU have confirmed the frequency of over-(25-58%) and underfeeding (12-35%). [45][46][47] Underfeeding has been linked to increased rates of total and infectious complications, 43 nosocomial bloodstream infection, 48 duration of mechanical ventilation, 49 ICU stay, 43 and mortality. 50 Impaired provision of protein increases fatigability, decreases strength and endurance, and promotes depletion of diaphragmatic muscles.…”
Section: General Remarksmentioning
confidence: 99%
“…However, a recent meta-analysis concluded that feeding critically ill patients with 25-66% of measured energy requirements may be sufficient, whereas increased amounts of calories improved clinical outcome in patients on enteral nutrition only [25]. Other authors suggest that patients receiving 90-100% of measured energy requirements should be considered as fed adequately [26], but that parenterally fed, critically ill patients should receive less energy than 36 kcal/kg per day [27].…”
Section: Energy Provision In Critically Ill Patientsmentioning
confidence: 99%